A Rapid Scoping Review of Gender Inequities in the Medical Profession - Ana M. Viamonte Ros; Sanford M. Markham; Diane Wu; Patrice K. Nicholas (Library & Knowledge Services and Nursing & Health Sciences Research Departments, 2019)
Introduction: There continue to be large inequities in the representation of women at progressive levels of training and seniority in both academic and community practice settings. Gender inequity in medicine is not only problematic in its own right but has the potential to deliver inequitable outcomes, including the neglect of important research and care that continues to disadvantage women patients. As significant evidence is emerging on gender inequities in the medical profession, it is an opportune time to review the current evidence on the persisting gaps, potential causes, and possible solutions. Methods: A rapid scoping review was conducted for articles on the topic of gender inequity and the medical profession in PubMed and Google Scholar. The search was limited to articles published from 1990 to the search date (June 1, 2017), and included only papers published in English. Results: An initial 1055 articles were screened according to established inclusion and exclusion criteria. After initial and full-text review, supplemented by a hand search through the article references, 45 articles were included in the review. Articles were classified as a) evidence for gender inequities, b) causes of inequities, and c) solutions for inequities. Only 13% of articles found (6 studies) addressed possible interventions to reduce inequities. Significant gaps exist in the literature, particularly around part-time work options, parental and family leave options, and ad-dressing implicit biases to reduce sexism in professional settings. Discussion: The evidence highlights substantial inequities in the representation of women in the medical profession, in both the academic and community settings, in medical literature, and in leadership positions. This review also highlighted substantial gaps in the literature on understanding what can be done to reduce these gaps. More research is needed in the area of gender inequities in medicine to improve the representation of women in medicine.